1998
DOI: 10.1007/s002449900288
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Hazard Assessment of Organochlorine Contaminants and Mercury in Smallmouth Bass from a Remote Lake in the Upper Peninsula of Michigan

Abstract: Concentrations of PCBs, DDTs, toxaphene, chlordanes, dieldrin, and mercury were determined in smallmouth bass (Micropterus dolomieui) collected from Fumee Lake, a remote lake in the Upper Peninsula of Michigan. An ecological hazard assessment was conducted to determine potential impacts of contaminants on bald eagles and mink eating fish from this lake. Concentrations of organochlorines, except toxaphene, and mercury in smallmouth bass were similar to those found in fish from Lake Superior, where atmospheric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…EPA, 1995b;Velleux et al, 1995;De Vault et al, 1996;Elder et al, 1996;Pirrone & Keeler, 1996;Giesy et al, 1997). A number of studies have indicated that Hg concentrations in the aquatic environment exceed state, federal, and/or international health guidelines (e.g., Food and Drug Administration [FDA] regulations for Hg levels in fish have been set at 1 mg/kg) (Pope & Rall, 1995;Mason & Sullivan, 1997;Henry et al, 1998). Investigators have also estimated the types of waterborne (e.g., 30-250 parts per trillion) Hg exposure scenarios 164 L. I.…”
Section: Sources Of Exposurementioning
confidence: 98%
“…EPA, 1995b;Velleux et al, 1995;De Vault et al, 1996;Elder et al, 1996;Pirrone & Keeler, 1996;Giesy et al, 1997). A number of studies have indicated that Hg concentrations in the aquatic environment exceed state, federal, and/or international health guidelines (e.g., Food and Drug Administration [FDA] regulations for Hg levels in fish have been set at 1 mg/kg) (Pope & Rall, 1995;Mason & Sullivan, 1997;Henry et al, 1998). Investigators have also estimated the types of waterborne (e.g., 30-250 parts per trillion) Hg exposure scenarios 164 L. I.…”
Section: Sources Of Exposurementioning
confidence: 98%
“…While humans can make a cognitive decision to include only those fish in their diets that have the highest benefits and the lowest Hg concentrations, wildlife have no such option. Mercury contamination in the Great Lakes region has been shown to threaten certain fish-consuming wildlife, including loons and mink, inducing negative effects such as reduced reproductive success, hormonal change, and motor skill impairment (Evers et al 1998;Henry et al 1998;Evers et al 2007, Burgess andMeyer 2008). Since wildlife face multiple ecological stressors such as variation in food supply, predation, habitat loss, disease, and human disturbance, limiting the amount of toxins they are exposed to can positively affect their health, reproduction, and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Mercuric chloride (HgCl 2 ) and the PCB congener Aroclor 1254 were selected because they are common anthropogenic contaminants in aquatic ecosystems. These persistent toxic contaminants are widespread and of recognised hazard in the Great Lakes [27,28], where lake trout are a native species. The following study was an attempt to determine if combinations of an environmental contaminant and an immunomodulatory agent could interact to produce toxicity greater than that of the environmental contaminant alone at concentrations typically encountered in piscine blood and other tissues.…”
Section: Introductionmentioning
confidence: 99%